2004
DOI: 10.1093/jn/134.11.3083
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Is Quickly Absorbed from Rat Stomach as the Free Form and Then Conjugated Mainly in Liver

Abstract: Ferulic acid (FA) is one of the most abundant phenolic antioxidants in the human diet. Many studies have documented its beneficial properties. It is therefore essential to understand the absorption and metabolism of FA in detail. The purpose of this study was to confirm the hypothesis that FA is absorbed in rat stomach and metabolized mainly in the liver. We determined the recovery of FA and its metabolites (FA sulfate/glucuronides) in rat gastric contents, gastric mucosa, portal vein plasma, celiac arterial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
174
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 195 publications
(187 citation statements)
references
References 32 publications
9
174
1
3
Order By: Relevance
“…The acute oral LD 50 of FA in male and female F344 rats was 2445 mg.kg -1 and 2133 mg.kg , respectively (Tada et al, 1999). Both free and linked FA are quickly absorbed from the stomach without modification due to acid pH, according to studies carried out in situ in the rat stomach, but it was verified that only the free form of the acid was absorbed by the intestine after administration of 8 µmol FA / kg body weight (Zhao et al, 2004).…”
Section: Preclinical Pharmacokineticmentioning
confidence: 99%
See 4 more Smart Citations
“…The acute oral LD 50 of FA in male and female F344 rats was 2445 mg.kg -1 and 2133 mg.kg , respectively (Tada et al, 1999). Both free and linked FA are quickly absorbed from the stomach without modification due to acid pH, according to studies carried out in situ in the rat stomach, but it was verified that only the free form of the acid was absorbed by the intestine after administration of 8 µmol FA / kg body weight (Zhao et al, 2004).…”
Section: Preclinical Pharmacokineticmentioning
confidence: 99%
“…Studies in humans and rats showed that after oral intake of FA, the most abundant metabolites generated in plasma were FA-glucuronide (FA conjugate with glucuronic acid) and FA-sulfoglucuronide (FA conjugate with sulfate and glucuronide) in addition to unmodified FA. The studies indicated that concentrations of metabolites derived from FA ingestion are a function of several factors such as the dose and route administered, as well as the animal species (Zhao et al, 2003(Zhao et al, , 2004.…”
Section: Preclinical Pharmacokineticmentioning
confidence: 99%
See 3 more Smart Citations